An empirical exploration of supply chain constraints facing the construction industry in South Africa - Pillay, Poobalan (Vaal University of Technology, 2016)
The South African Construction Industry is one of the largest contributors to the gross domestic product of the country as well as to employment. It has, however, been experiencing significant challenges due to multifaceted factors. The main objective of this research was to identify the supply chain management constraints within the South African Construction Industry and how these can be overcome. This study is by nature descriptive and exploratory and contains qualitative elements. The problems were identified through a literature review, focused group discussions and interviews with major construction companies in South Africa. The findings also indicate that the main supply chain management constraints are to a greater extent internal and typical of supply chain methodologies and approaches. These constraints are among others the lack of coordination, collaboration and commitment between suppliers and clients within the supply chain, poor leadership in key areas of systems, design problems (many changes and inconsistent information), deficient internal and external communication and information transfer, inadequate management within the supply chain, mainly poor planning and control just to mention a few. A model based on supply chain system management as well as the Theory Of Constraints (TOC) has been developed that can be a useful tool to address the constraints in the construction sector. Originating from the study are applicable recommendations for the South African construction industry supply chains, covering key themes that have been articulated in the study, particularly benchmarking to the theory of constrains. Such recommendations include further research core components of supply chain such as, collaborations, logistics and how each of system components can be linked to performance of the supply chain management system.
D. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supply chain management; Theory of constraints; Construction industry; Dissertations, Academic -- South Africa.; Business logistics -- South Africa.; Construction industry -- South Africa.